Political research : an introduction - Harrison, Lisa (Routledge, 2020)
Political Research: An Introduction has been designed to provide an excellent starting point for those new to the area of Research Methods. It assumes no prior knowledge of the subject and sets out the key issues involved in doing research in Politics. It guides students through a complex and often daunting subject by exploring the many concepts associated with the field, as well as offering practical advice on research practices and information resources.